2015
DOI: 10.2147/vhrm.s79198
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin/Simvastatin: a first combination tablet to treat type 2 diabetes and hypercholesterolemia – a review of its characteristics

Abstract: BackgroundThe purpose of this study was to review the current literature and information on the combination product Juvisync™ (sitagliptin + simvastatin), which was approved by the US Food and Drug Administration in October 2011.MethodsPubMed (2001–2014) was searched for primary and review articles on sitagliptin, simvastatin, or the combination product. Drug manufacturing data and product labeling were also used. Studies of simvastatin, sitagliptin, or the combination were screened and analyzed to include rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The choice of an insulin treatment, timely initiation and schedule of insulin therapy are crucial factors in reaching optimal glycemic control. This involves a proper combination of insulin and antidiabetic agents in a way that guarantees safety and improves blood glucose levels (Table I) (29)(30)(31)(32)(33)(34)(35).…”
Section: Diabetes and Drug Treatmentsmentioning
confidence: 99%
“…The choice of an insulin treatment, timely initiation and schedule of insulin therapy are crucial factors in reaching optimal glycemic control. This involves a proper combination of insulin and antidiabetic agents in a way that guarantees safety and improves blood glucose levels (Table I) (29)(30)(31)(32)(33)(34)(35).…”
Section: Diabetes and Drug Treatmentsmentioning
confidence: 99%
“…Simvastatin is a statin that is a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, which is currently used to manage blood cholesterol levels and prevent cardiovascular disease (10,11). It has been reported that simvastatin increases the survival of patients with sepsis or infection by inhibiting sepsis-induced mortality and preventing acute kidney injury (12).…”
Section: Introductionmentioning
confidence: 99%
“…Further putative therapeutic effects include decrease of hippocampal amyloid-beta abundance in Alzheimer’s disease [16], anticoagulation [10], inhibition of inflammatory disease, such as asthma [1, 17-19], protection against contrast-induced nephropathy [20], protection of cardiac allografts against ischemia/reperfusion injury [21], as well as counteraction of osteoporosis and support of bone fracture healing [22, 23]. Side effects of simvastatin include rhabdomyolysis [6, 8, 24-29] and thrombocytopenia [30]. …”
Section: Introductionmentioning
confidence: 99%